Acute Cobalt-Induced Lung Injury and the Role of Hypoxia-Inducible Factor 1α in Modulating Inflammation - Saini, Yogesh (Oxford University Press, 2010)
Air pollution is a critical factor in the development and exacerbation of pulmonary diseases. Ozone, automobile exhaust, cigarette smoke, and metallic dust are among the potentially harmful pollution components that are linked to disease progression. Transition metals, such as cobalt, have been identified at significant levels in air pollution. Cobalt exerts numerous biological effects, including mimicking hypoxia. Similar to hypoxia, cobalt exposure results in the stabilization of hypoxia-inducible factors (HIFs), a family of proteins that regulate the cellular response to oxygen deficit. HIFs also play an important role in innate immunity and inflammatory processes. To characterize the role of HIF1α, the most ubiquitously expressed HIF, in the early events during cobalt-induced lung inflammation, an inducible lung-specific HIF1α deletion model was employed. Control mice showed classical signs of metal-induced injury following cobalt exposure, including neutrophilic infiltration and induction of Th1 cytokines. In contrast, HIF1α-deficient mice exhibited pronounced eosinophil counts in bronchoalveolar lavage fluid and lung tissue complemented with Th2 cytokine induction. The timing of these results suggests that the loss of epithelial-derived HIF1α alters the lung's innate immune response and biases the tissue toward a Th2-mediated inflammation.